Perancangan Ulang Lintasan Produksi Cell Assembly Connector 3P di PT. Schneider Electric Manufacturing Batam menggunakan Metode Line Architecture Design Methodology - Julius Oscar; Herry Christian Palit (Jurnal Titra, 2022)
PT. Schneider Electric Manufacturing Batam will efficiently redesign the cell assembly connector 3P production line for Everlink 3P, Everlink 4P and the new GZ3 product. The redesign was carried out using the Line Architecture Design Methodology. With the Customer Demand for the three products of 346.63 Pcs/Hr, an architectural design was produced with a total of 3 cells, 2 operators per cell and 3 operations per cell and additional benches to overcome production capacity problems. The new design can produce 384 Pcs/Hrs so that it can meet Customer Demand until 2025. In actual application, the company makes architectural designs with 1 cell, 6 operators per cell and 8 operations per cell. The actual design is not suitable in terms of workload and elasticity, but it can still run to meet the number of consumer demands. Meanwhile, in terms of ergonomics, it is still classified as medium level, which means it is still allowed to operate.